Breaking Down the Pseudo-Pacification Process: Eight Critiques of Ultra-Realist Crime Causation Theory. (3rd November 2019) - Wood, Mark A; Anderson, Briony; Richards, Imogen
Abstract: This paper critically examines ultra-realist criminology's two central crime causation theories: the breakdown of the pseudo-pacification process and special liberty. We identify a number of shortcomings in these theories pertaining to (1) their explanation of gender-related disparities in criminal offending; (2) their explanation of violence reduction through Freudian notions of drives, libidinal energy, and sublimation; and (3) their explication of crime as an expression of capitalist values. Fundamentally, we suggest that in treating political economy as the underlying source of all causative power in society, both theories engage in what Margaret Archer terms 'downwards conflationism'. To this end, ultra-realism offers what we term a 'direct expression theory of crime', in which crime is a synecdoche and direct unmediated expression of political-economic conditions alone. Drawing on Margaret Archer's realist social theory, we conclude by sketching out several potential principles of an 'indirect expression theory' that avoid the shortcomings of ultra-realism in explaining the complicated relationship between political economy and crime.